The Return of Class Analysis: Reviewing the Methodological Contributions of Jenny Clegg’s Storming the Heavens: Peasants and Revolution in China, 1925-1949 viewed Through A Marxist Lens (World Marxist Review, 2026)
Since the 1980s, a quiet shift has occurred in the field of Western research on Chinese peasants. Philip Huang used "involution" to explain rural stagnation; Elizabeth Perry used localism and clan networks to explain peasant resistance; Ralph Thaxton used "moral economy" to explain the motivations behind peasant rebellion. While each of these frameworks offers specific insights, they share a commonality: they avoid or dissolve class analysis. Concurrently, within China, neoliberal discourses represented by Qin Hui have been systematically denying the legitimacy of the land revolution, portraying traditional Chinese society as a society of owner-cultivators oppressed by "Asiatic despotism", thereby hollowing out the class basis for peasant revolution.